(untitled) (Fiep Bulletin - online, 2014)
Focalized in the work of Dartagnan Pinto Guedes and Elisabete Joana Ribeiro Pinto Guedes (GUEDES & GUEDES, 1993; 2001), dealing mainly to Physical Education focused on the human being’s life prolongation through an education for the health since child serving as a stimulus for the continuity in research that will complete the inexhaustible collection that transits about HEALTH at school, and for the life, has been made this work. The modern times, in particular the era of industrialization, brought many technological advances with an amazing speed. Some also brought losses to the population, because such benefits decreased the daily physical expense of energy and this are linked to several diseases, including hypertension, diabetes, anxiety (stress), obesity and cholesterol’s increase. It is known that the correct implementation of physical activities, as well as a systematized monitored orientation, is important to all individuals. Starting from this vision, we propose a program focalized and adjusted as needed in question. The program was conducted on a racecourse for the practice of hiking, the academic methodology used in a systematic guidance, as follows: An initial interview, determined to achieve the goals of treatment; Determine the area of training of the individual, taking into account their goals and their physical limitations or pathological. Starting the proposed physical activities, divided into three parts, they are: The heart rate (HR) and blood pressure (BP), they were checked and recorded every 5 minutes. This monitoring was carried out by a multidisciplinary team compounded by 2 physiotherapists, 1 FAEFIJA’s professor and trainees who are students of the Faculty of Physical Education and Physiotherapy, achieving, thus, multiply the agent of the educational regular practice of physical activities.